(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Summary and Plagiarism Prevention: A Comprehensive Guide" is an informative article that explores the importance of effective summarizing techniques and the crucial role they play in preventing plagiarism. The article highlights the significance of summarizing as a tool for condensing information, enhancing comprehension, and retaining key points. It delves into various summarizing strategies, such as identifying main ideas, using paraphrasing techniques, and maintaining objectivity.Furthermore, the article addresses the pressing issue of plagiarism and offers practical tips on how to prevent it. It elaborates on the ethical consequences of using someone else’s work without proper acknowledgement and emphasizes the need for citing sources correctly. The authors provide valuable insights into the different types of plagiarism, including direct copying, paraphrasing without attribution, and self-plagiarism.This article serves as an essential resource for students, educators, and professionals seeking to enhance their summarizing skills and avoid plagiarism.Researches of Charles, M., &Pecorari, D., Hyland, K.,Kocatepe, M., and many others were analyzed and discussed in this article.